Electrochemical noise studies on localized corrosion of Ni and Ni-20Cr in molten ZnCl2. (1st November 2022) - Sure, Jagadeesh; Gill, Simerjeet k; Wang, Yachun; Bawane, Kaustubh.K.; He, Lingfeng; Halstenberg, Phillip; Dai, Sheng; Mahurin, Shannon M.; Wishart, James F.; Sasaki, Kotaro
Abstract: The electrochemical noise (ECN) technique was employed to study corrosion of two model systems, i.e . pure Ni and a binary Ni-20 wt%Cr (Ni20Cr) alloy in molten ZnCl2 at 623 K. We measured ECN transients in current and open-circuit potential from two nominally identical Ni-Ni and Ni20Cr-Ni20Cr electrodes and one galvanic Ni-Ni20Cr electrode pair. The behavior of ECN is quite distinct among the three-electrode systems, and it is correlated with the various microscopic observations of micro- and nano-scale morphological features. Based on the ECN study coupled with the microstructural analysis, the origins of ECN in the molten salt environment as well as the mechanisms of localized corrosion in the three systems are discussed.